Variations in Ionospheric Total Electron Content and Scintillation at GPS stations in Uzbekistan and China during the Annular Solar Eclipse on June 21, 2020 - Eshkuvatov, H. E.; Jamjareegulgarn, Punyawi; Ahmedov, B. J.; Tillayev, Y. A.; Ruziev, Z. J.; Kosbergenov, E. Zh; Abdullayev, N. Q.; Liu, Libo; Sayfulloyev, Sh A.; Musurmonov, M. A. (My University, 2025)
This study presents a novel investigation into the distinct ionospheric variations observed over China and Uzbekistan during the annular solar eclipse on June 21, 2020. For the first time, we demonstrate the influence of this celestial event on Total Electron Content (TEC) measurements obtained from GPS satellites. We analyzed fluctuations in TEC and the Ionospheric Scintillation Index (S4) across six strategically selected sites—three in Uzbekistan (MTAL, KIT3, MADK) and three in China (JFNG, LHAZ, BJFS) located near the eclipse path, with obscuration levels of 52%, 57%, 58%, in Uzbekistan and 92%, 94% and 95% in China. Our study involved continuous monitoring of ionospheric parameters over three days, from June 20 to June 22, 2020. Results indicated a significant TEC depletion ranging from 10% to 30% on the day of the eclipse. The analysis reveals that both TEC levels and the S4 scintillation index experienced notable reductions during the event, attributed to the decreased ionizing radiation. These findings enhance our understanding of ionospheric dynamics in response to solar eclipses and have important implications for satellite communication and navigation systems.
Keywords: GNSS; GPS; Ionosphere; Scintillation; Solar eclipse; TEC